RESPON PEMBERIAN BERBAGAI DOSIS PUPUK BOKASHI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) LOKAL KONAWE - MUSAHIDIN, REZKI; KARIMUNA, LA; RAHNI, NINI MILA; ADAWIYAH, ROBIATUL (Jurnal Agroteknos, 2022)
This study aims to determine the effect of various doses of bokashi fertilizer on the growth response and production of local Konawe corn plants and to determine which treatment has the best effect on the application of various doses of bokashi fertilizer on the growth response and production of local corn plants in Konawe. This research took place at the Field Laboratory of Experimental Gardens II, Faculty of Agriculture, Halu Oleo University, Kendari. From January to March 2021. This study used a randomized block design consisting of 5 levels of treatment, namely control without bokashi fertilizer (B0), bokashi fertilizer 5 t ha-1(B1), bokashi fertilizer 10 t ha-1 (B2), bokashi fertilizer 15 t ha-1 (B3), bokashi fertilizer 20 t ha-1 (B4). Each treatment was repeated 3 times so that there were 15 experimental units. The results showed that the observed variables had a very significant effect on plant height, stem diameter, number of leaves, leaf area, cob weight, ear length (cm), wind-dried shell weight, weight of 100 seeds and productivity. The best treatment was obtained at doses of bokashi fertilizer of 20 t ha-1 (B4) and 15 t ha-1 (B3).